1998
DOI: 10.1111/j.1600-9657.1998.tb00854.x
|View full text |Cite
|
Sign up to set email alerts
|

Mandibular central incisor with two root canals

Abstract: A case report of a mandibular central incisor with two root canals and two separate apical foramina is presented. The tooth showed inadequate endodontic treatment and a periapical radiolucent lesion. The lesion healed following endodontic retreatment and proper obturation of both root canals.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0
5

Year Published

2005
2005
2020
2020

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 4 publications
0
10
0
5
Order By: Relevance
“…a) or two periapical radiolucent areas around the root surface may also suggest the presence of an extra root/root canal (Funato et al . , Lin et al . ).…”
Section: Literature Search Methodologymentioning
confidence: 99%
See 1 more Smart Citation
“…a) or two periapical radiolucent areas around the root surface may also suggest the presence of an extra root/root canal (Funato et al . , Lin et al . ).…”
Section: Literature Search Methodologymentioning
confidence: 99%
“…In teeth with necrotic pulps, the presence of an apical rarefaction on the lateral side of the root (Fig. 1a) or two periapical radiolucent areas around the root surface may also suggest the presence of an extra root/root canal (Funato et al 1998, Lin et al 2006).…”
Section: Identification Landmarksmentioning
confidence: 99%
“…The root canal morphology of mandibular central and lateral incisors is very similar. Although they have only one root and a high prevalence of Type 1 root canal morphology, surgical and nonsurgical root canal treatment may fail in these teeth if there is a lack of awareness in their internal anatomy which is complicated by the presence of the lingual canal, bifurcation, lateral anatomy, and isthmus [17,29]. The morphological characteristics of the root canal system were studied using a number of techniques [18,27,30].…”
Section: Number Of Canals In Permanent Mandibular Incisorsmentioning
confidence: 99%
“…However the occurrence of two root canals with two separate foramina (Vertucci type IV) in the mandibular incisors is very rare viz 3% and 2% in the mandibular central incsors and lateral incisors respectively, and in canines it is 6%.Funato A et al 10 has reported a case with two root canals and seprate apical foamina in the mandibular central incisor.…”
Section: …………………………………………………………………………………………………… Introduction:-mentioning
confidence: 99%